2016
DOI: 10.1007/s13659-016-0111-9
|View full text |Cite
|
Sign up to set email alerts
|

Lyconadins G and H, Two Rare Lyconadin-Type Lycopodium Alkaloids from Lycopodium complanatum

Abstract: Two rare lyconadin-type Lycopodium alkaloids, lyconadins G (1) and H (2), together with four known ones (3–6), were isolated from Lycopodium complanatum. The structures were determined on the basis of their spectroscopic analyses, and the absolute configuration of 1 was established by an X-ray crystallographic analysis. It is the first time to establish the absolute configuration of lyconadin-type Lycopodium alkaloid by an X-ray diffraction experiment. In addition, these findings may provide more information f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The lycopodium alkaloids are isolated from club mosses, which have been widely used in traditional medicines. Many of the lycopodium alkaloids have reported biological activity, including enhanced mRNA expression of neurotropic growth factor , and anticancer activity in different cell lines . Lycopodium alkaloids have inspired synthetic chemists for generations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lycopodium alkaloids are isolated from club mosses, which have been widely used in traditional medicines. Many of the lycopodium alkaloids have reported biological activity, including enhanced mRNA expression of neurotropic growth factor , and anticancer activity in different cell lines . Lycopodium alkaloids have inspired synthetic chemists for generations .…”
Section: Introductionmentioning
confidence: 99%
“…Lycopodium alkaloids have inspired synthetic chemists for generations . Himeradine A has attracted the interest of organic chemists. , The structurally similar lyconadine family of natural products have generated a great deal of interest and a variety of creative synthetic strategies . Syntheses of Lycopodium alkaloids has been recently reviewed …”
Section: Introductionmentioning
confidence: 99%
“…Recent research on Lyconadins have reported Lyconadins C-E along with previously reported Lyconadin A and Lyconadin B. Cheng et al (2016), have reported the presence of rare lyconadin G and lyconadin H in L. complanatum. Lyconadins have also been reported to show modest cytotoxicity against human epidermal carcinoma KB cells and murine lymphoma L1210 cells (Kobayashi et al, 2001).…”
Section: Lycopodium Derived Alkaloidsmentioning
confidence: 69%
“…The lycopodium alkaloids are a structurally diverse group of natural products containing more than 300 alkaloids isolated from 54 Lycopodium species . These natural products display encouraging biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…These natural products display encouraging biological activities. For example, recent studies revealed that some lycopodium alkaloids like huperzine A could inhibit acetylcholinesterase, improve efficiency for learning and memory in animals, and therefore show potential in treatment of Alzheimer's disease . In addition, lyconadin A exhibited micromolar cytotoxicity against murine lymphoma L1210 and human epidermoid carcinoma KB cells, while lyconadins A and B could enhance the mRNA expression for nerve growth factor in 1321N1 human astrocytoma cells .…”
Section: Introductionmentioning
confidence: 99%